1994
DOI: 10.1007/bf00158593
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemical demonstration of chymase and tryptase in human intestinal mast cells

Abstract: An immunohistochemical double-labelling technique for the simultaneous identification of mast cells containing tryptase alone (MCT) or chymase together with tryptase (MCTC) was evaluated quantitatively using two monoclonal antibodies, mAb 1222A (antitryptase) and mAb 1254B (antichymase). Saturation conditions were established for the binding of the antibodies to the mast cell enzymes by counting labelled mast cells in consecutive sections of normal human intestine incubated with serial dilutions of the antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…On the other hand, in the presence of conditioned medium from fibroblasts, we and others were able to obtain a majority of completely mature cells, resembling skin and peritoneal mast cells [54,55], and expressing chymase and/or tryptase, suggesting the presence of at least two populations of mast cells: MC T (containing only tryptase) and MC TC (containing both tryptase and chymase). Although double immunostaining was not performed to show the colocalization of these proteases, the percentage of the Try-ir and Chy-ir cells was not significantly different, therefore suggesting their coexistence within the same cells as has been demonstrated by others [56,[60][61][62][63]. Indeed, the existence of cells containing only chymase [64,65] is a subject of controversy because different groups failed to detect such cells [57,61].…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, in the presence of conditioned medium from fibroblasts, we and others were able to obtain a majority of completely mature cells, resembling skin and peritoneal mast cells [54,55], and expressing chymase and/or tryptase, suggesting the presence of at least two populations of mast cells: MC T (containing only tryptase) and MC TC (containing both tryptase and chymase). Although double immunostaining was not performed to show the colocalization of these proteases, the percentage of the Try-ir and Chy-ir cells was not significantly different, therefore suggesting their coexistence within the same cells as has been demonstrated by others [56,[60][61][62][63]. Indeed, the existence of cells containing only chymase [64,65] is a subject of controversy because different groups failed to detect such cells [57,61].…”
Section: Discussionmentioning
confidence: 91%
“…Finally, many studies showed that tryptase originating from mast cells, also activates PAR-2 (Mirza et al, 1997;Molino et al, 1997a;Akers et al, 2000) though with a reduced potency and efficacy as compared to trypsin (Molino et al, 1997a). Since mast cells are abundant in colonic mucosa (Aldenborg and Enerback, 1994) and have been found to infiltrate colon tumour, it can be suggested that tryptase is a putative activator of PAR-2 in colonic tumours. In our recent studies, we showed that tryptase was also able to promote colonic cancer cell proliferation (Darmoul et al, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are abundant in the normal colon (20), and intestinal manipulation and inflammation are associated with an influx and degranulation of mast cells (21)(22)(23). Further experiments are required to determine if activation of PAR-2 by tryptase contributes to disorders of intestinal motility, such as postoperative ileus (41), that accompany mast cell infiltration and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although PAR-2 mRNA is highly expressed in the colon (3,6), its cellular location, mechanism of activation, and biological functions are unknown. Mast cells are normally present in the colon (20), and intestinal manipulation and inflammation result in mast cell infiltration, degranulation, and tryptase release (21)(22)(23). Tryptase may activate PAR-2 and thereby contribute to functional disturbances that accompany mast cell infiltration and degranulation in the colon.…”
Section: Introductionmentioning
confidence: 99%